Fraudulent Financial Statement on The Property and Real Estate Sector in Indonesia and Malaysia - Jati, Kuat Waluyo; Setiyani, Nur Anisa’ (Department of Accounting, Faculty of Economics, Universitas Negeri Semarang, 2023)
Purposes: The research aims to test and determine the influence of the components in the fraud hexagon on fraudulent financial statements.Methods: The population in this research are property and real estate sector companies listed on the Indonesia Stock Exchange and Malaysia Stock Exchange in 2020-2022. The study’s sampling technique used purposive sampling to obtain 77 companies with 187 units of analysis. Data were analyzed by panel data regression analysis using Eviews 12.Findings: The results show that financial targets, the nature of the industry, and ineffective monitoring positively and significantly affect fraudulent financial statements. Meanwhile, external pressure and the frequent number of CEO pictures reduce fraudulent financial statements. As for director experience, political connections and changes in auditors do not affect fraudulent financial statements.Novelty: Novelty in this research, namely the use of populations in Indonesia and Malaysia. The proxy used to represent the capability element also uses the director experience variable, which is rarely used in previous research.